2022
DOI: 10.1186/s12871-022-01641-5
|View full text |Cite
|
Sign up to set email alerts
|

Application effects of remimazolam and propofol on elderly patients undergoing hip replacement

Abstract: Objective To explore the anesthetic and analgesic effects of remimazolam and propofol in elderly patients undergoing hip replacement and their effects on respiratory and circulatory systems, stress and cognitive function. Methods Sixty elderly patients undergoing elective hip replacement in the hospital were selected as the research subjects, and they were divided into the remimazolam group and the propofol group according to the admission sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 20 publications
1
38
1
1
Order By: Relevance
“…This may be because remimazolam can act on adrenergic receptors, inhibit norepinephrine release, and reduce the catecholamine level as well as sympathetic nerve excitability, however remimazolam can accelerate atrioventricular conduction and enhance myocardial contractility. [8] The use of esmolol is ideal for suppressing sympathetic stimulation, thereby decreasing the LVOT gradient and improving the cardiac output. [9] The DoA was monitored using CFSi based on electroencephalogram in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because remimazolam can act on adrenergic receptors, inhibit norepinephrine release, and reduce the catecholamine level as well as sympathetic nerve excitability, however remimazolam can accelerate atrioventricular conduction and enhance myocardial contractility. [8] The use of esmolol is ideal for suppressing sympathetic stimulation, thereby decreasing the LVOT gradient and improving the cardiac output. [9] The DoA was monitored using CFSi based on electroencephalogram in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Total intravenous anaesthesia with remimazolam tosylate causes minimal haemodynamic and respiratory depression in elderly patients. Compared with propofol, remimazolam tosylate may have an equivalent anaesthetic effect and a higher safety profile for elderly patients undergoing hip replacement, gastrointestinal endoscopy, bronchoscopy and general anaesthesia 56–58. Moreover, previous literature has also proven remimazolam tosylate’s availability as a general anaesthetic for continuous infusions during procedures longer than 2 hours 59.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with propofol, remimazolam tosylate may have an equivalent anaesthetic effect and a higher safety profile for elderly patients undergoing hip replacement, gastrointestinal endoscopy, bronchoscopy and general anaesthesia. 56–58 Moreover, previous literature has also proven remimazolam tosylate’s availability as a general anaesthetic for continuous infusions during procedures longer than 2 hours. 59 However, research on the effect of remimazolam tosylate on the incidence of POD is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that remimazolam is safer than propofol in terms of stable hemodynamic changes (1,4,5,9). Compared with propofol, remimazolam has the advantage of preventing hypotension during the induction of anesthesia and similar anesthetic effects in elderly patients (10,11). However, there is insufficient evidence regarding the efficacy and safety of remimazolam in elderly patients, and it is unknown whether remimazolam can be used safely and effectively in elderly patients at the clinical doses proposed by manufacturers.…”
Section: Introductionmentioning
confidence: 99%